Self-esteem and technological unemployment: should we halt AI to protect meaningful work? - Cordasco, Carlo Ludovico (Journal of business ethics, 2025)
Should we insulate humanity from AI development in an effort to preserve people’s ability to form self-esteem and find meaning in their occupations? In this article, we take this possibility seriously and argue that technological insulation would ultimately fail in its aim. In doing so, we will consider two different scenarios: one in which we only halt the deployment of technology that would lead to our replacement as workers, and a second one in which we collectively deliberate to halt technological development as a whole. The former, we argue, fails to preserve our ability to form self-esteem, as we become aware that our role is contingent on a policy that artificially preserves our status as contributing members of our communities. The latter seems unfeasible and overly demanding considering the expected benefits of AI. We propose instead the life of play and the life of excellence in the context of collaborative work with machines as alternative sources of self-esteem to the life of work.